Treatment of horseshoe fistula with a two‐stage modified Hanley procedure: A video vignette. (31st July 2022) - Leventoglu, Sezai; Balci, Bengi; Yildiz, Alp; Mentes, Bedrettin Bulent
Abstract: A horseshoe fistula is a complex fistula that needs to be appropriately recognized to decrease recurrence rates usually resulting from insufficient treatment. The video presents a modified Hanley procedure for horseshoe fistula.